Weak d0 ferromagnetism: Zn vacancy condensation in ZnS nanocrystals. (14th November 2016) - Proshchenko, Vitaly; Dahnovsky, Yuri
Abstract: We provide the explanation of the large discrepancy of three orders of magnitude between the experimentally measured and theoretically calculated magnetic moments in ZnS nanocrystals. We assume that the condensation of Zn vacancies into a single droplet takes place. The energy calculations reveal that the droplet phase is more favorable than the uniformly distributed vacancy configuration. The other assumption made is that a small magnetic moment could arise at the interface between the ZnS crystal and vacancy cluster. The calculations however dismiss this hypothesis because the magnetization of the layered system also vanishes. Thus we suggest that the experimentally low magnetization values could be explained from one of the two following pictures: (a) there are two phases where the vacancy cluster with the zero magnetic moment coexists along with the other phase, in which there are uniformly distributed Zn vacancies with low concentrations or (b) there is only a single vacancy phase—a vacancy droplet being in the metastable state with a weak nonvanishing magnetic moment.